Laparoscopic duodenum-preserving pancreatic head resection: A case report. Issue 32 (August 2016) - Zhou, Jiayu; Zhou, Yucheng; Mou, Yiping; Xia, Tao; Xu, Xiaowu; Jin, Weiwei; Zhang, Renchao; Lu, Chao; Chen, Ronggao
Abstract: Background: Solid pseudopapillary neoplasms (SPNs) of the pancreas are uncommon neoplasms and are potentially malignant. Complete resection is advised due to rare recurrence and metastasis. Duodenum-preserving pancreatic head resection (DPPHR) is indicated for SPNs located in the pancreatic head and is only performed using the open approach. To the best of our knowledge, there are no reports describing laparoscopic DPPHR (LDPPHR) for SPNs. Methods: Herein, we report a case of 41-year-old female presented with a 1-week history of epigastric abdominal discomfort, and founded an SPN of the pancreatic head by abdominal computed tomography/magnetic resonance, who was treated by radical LDPPHR without complications, such as pancreatic fistula and bile leakage. Histological examination of the resected specimen confirmed the diagnosis of SPN. Results: The patient was discharged 1 week after surgery following an uneventful postoperative period. She was followed up 3 months without readmission and local recurrence according to abdominal ultrasound. Conclusion: LDPPHR is a safe, feasible, and effective surgical procedure for SPNs.